Ensino religioso no contexto da escola indígena Potiguara da Paraíba - Santana Neto, Daniel (2023)
This research is of great relevance for the academic field and the Potiguara - PB ethnic group, as it presents a reality of Religious Education (RE), of schools located in the Potiguara - PB indigenous villages, starting from a historical social, cultural and educational context of this people. The general objective is to analyze the practice of religious teaching in the Potiguara indigenous school in Paraiba for the understanding of the cultural and religious plurality of all that integrate the school environment. The research and the structure of the text dialogue with the thinking of Vieira (2012; 2021), Barcellos and Holmes (2021), Vilhena (2005), Sena (2007), Mendonça (2022), Oliveira et al (2007), among many others. other theorists who discuss Religious Education and the history of the Potiguara - PB people. The study is based on Brazilian legislation and texts that contemplate Religious Education. The methodology has a qualitative approach with emphasis on the case study method, considering some instruments for data collection, such as: field diary, interview and participant observation. The research field is the indigenous schools of the villages: Alto do Tambá, São Francisco, Silva da Estrada, and Antônio Azevedo, in the center of the city of Baía da Traição. Teachers, students, directors and indigenous pedagogical coordinators were interviewed. As a result, a holistic view of the reality of Religious Education in schools in indigenous villages and in the city center of Baía da Traição - PB is presented. The results of this research reveal that Religious Education is part of the Curricular Matrix of schools in the municipality of Baia da Traição - PB, training in the area of knowledge of Religious Education is fundamental for teachers who teach the curricular component, teaching works diversity religious and cultural, contemplating the differences and realities of the students.